Dasar Pertimbangan Hukum Hakim Menjatuhkan Putusan Lepas Dari Segala Tuntutan Hukum Terdakwa Dalam Perkara Penipuan - Syarifah Dewi Indawati (Verstek, 2017)
Research was to determine the conformity consideration the judge of Denpasar District Superior Court in releasing the defendant from any lawsuit in fraudulence cases with the provisions of Criminal Procedure Code.     Based on the research and resulting conclusions set forth discussion, basis consideration the judge in drop down the Verdict Loose From the Guilt in case Number: 24/PID/2015.PT.DPS that the judge in deciding the case based on the facts revealed at courts by examine some of the evidence and the existence of agreements which conducted by both parties beforehand that payment terms of purchase agreement within range Two (2) months, which can not be interpreted as fraudulence so that a legal relationship well built are the legal relationship of civil not a legal relationship of penal law, so the judge believes that factors existing in Article 378 which the basis Public Prosecutor demands not completely fulfilled.       Keywords: Loose From the Guilt, An Appeal, Basis Consideration Of The Judge.